Getting out of a tight spot: Cooperative unclogging of hydrogel particles in disordered porous media - Sanjana Kamath; Laurent Talon; Meera Ramaswamy; Christopher A. Browne; Sujit S. Datta (Physical Review Research, 2025)
We use event-driven pore network modeling to study the transport of hydrogel particles through disordered porous media—a process that underlies diverse applications. By simulating particle advection, deformation, and clogging at the pore scale, we identify a dimensionless “squeezing parameter” that quantitatively predicts the depth to which particles penetrate into a given medium across diverse conditions. Our simulations also uncover a surprising cooperative effect: Adding more particles enables them to penetrate deeper into the medium. This phenomenon arises because individual particles redirect fluid to adjacent throats, forcing nearby particles through tight pores that they would otherwise clog. Altogether, these results help to establish a quantitative framework that connects microscopic particle mechanics to macroscopic transport behavior.